2017
DOI: 10.1534/genetics.116.199323
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis Identifies Orthologs of Human Chitinase-Like Proteins as Inducers of Tube Morphogenesis Defects inDrosophila melanogaster

Abstract: Elevated levels of human chitinase-like proteins (CLPs) are associated with numerous chronic inflammatory diseases and several cancers, often correlating with poor prognosis. Nevertheless, there is scant knowledge of their function. The CLPs normally mediate immune responses and wound healing and, when upregulated, they can promote disease progression by remodeling tissue, activating signaling cascades, stimulating proliferation and migration, and by regulating adhesion. We identified Imaginal disc growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
2
24
1
Order By: Relevance
“…If so, the RNAi-mediated reduction of s38-protein content below a certain threshold can sensitize choriogenesis to stochastic variation in morphogenetic events and also disable or weaken negative-feedback-loop’s strength, leading to the diverse dysmorphias obtained and the different s38 -gene transcription activities observed between dysmorphic follicles carrying short or comparatively longer dorsal appendages. Interestingly, a similar type of incomplete penetrance has been recently described, suggesting a role of Idgfs (Imaginal disc growth factors) in the stochastic variation regarding coordination and timing of events during dorsal-appendages morphogenesis 50 .…”
Section: Discussionsupporting
confidence: 54%
“…If so, the RNAi-mediated reduction of s38-protein content below a certain threshold can sensitize choriogenesis to stochastic variation in morphogenetic events and also disable or weaken negative-feedback-loop’s strength, leading to the diverse dysmorphias obtained and the different s38 -gene transcription activities observed between dysmorphic follicles carrying short or comparatively longer dorsal appendages. Interestingly, a similar type of incomplete penetrance has been recently described, suggesting a role of Idgfs (Imaginal disc growth factors) in the stochastic variation regarding coordination and timing of events during dorsal-appendages morphogenesis 50 .…”
Section: Discussionsupporting
confidence: 54%
“…The mammalian ortholog of IDGF4 is OVGP1, also known as oviductal glycoprotein 1 [37]. We observed that the dMLL3/4-regulated glycosyl hydrolase IDGF4 has a mitogenic effect on the early embryo.…”
Section: Discussionmentioning
confidence: 79%
“…We observed that the dMLL3/4-regulated glycosyl hydrolase IDGF4 has a mitogenic effect on the early embryo. The mammalian ortholog of IDGF4 is OVGP1, also known as oviductal glycoprotein 1 [37]. OVGP1 localizes to the oviduct-the site of mammalian fertilization-where it has been shown to be a component of the extracellular matrix of ovulated oocytes and early embryos [50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowering the expression of Idgf4, Idgf5, or Idgf6 ameliorates the bwk mutant phenotype, suggesting they are part of the bwk signaling pathway that regulates dorsal appendage formation. Up-regulating only a single member of this family, e.g., Idgf3, is sufficient to produce a phenotype similar to the bwk mutant ( Figure 1D) (Zimmerman et al 2017).…”
mentioning
confidence: 97%